COOLING PHOTOVOLTAIC SYSTEMS: A SURVEY OF AVAILABLE TECHNOLOGIES - Siecker, J.; Kusakana, K. (My University, 2017)
Cooling is a key operation factor to take into consideration to achieve higher efficiency when operating solar photovoltaic systems. Proper cooling can improve the electrical efficiency, and the heat removed by the cooling system can be used in other domestic, commercial or industrial applications. This paper is a survey of various methods that can be used to minimize the negative impacts of the increased temperature while making an attempt to enhance the efficiency of photovoltaic solar panels operating beyond the recommended temperature from the Standard Test Conditions (STC). These technologies are discussed based on their operation principles, technical advantages, and disadvantages. The results of this study highlight that any technology selected to cool a photovoltaic panel should be used to keep the operating surface temperature low and steady, be simple and reliable and, if possible, enable the use of extracted thermal heat to enhance efficiency of the overall conversion system.
Article
Keywords: Solar photovoltaic; cooling technologies; conversion efficiency